Infantile Anorexia and Co-parenting: A Pilot Study on Mother–Father–Child Triadic Interactions during Feeding and Play - Lucarelli, Loredana; Ammaniti, Massimo; Porreca, Alessio; Simonelli, Alessandra (Frontiers in Psychology, 2017)
Infantile Anorexia (IA), defined by the Diagnostic Classification of Mental Health and Developmental Disorders of Infancy and Early Childhood Revised (DC: 0-3R, Zero-To-Three, 2005), occurs when the child (a) refuses to eat adequate amounts of food for at least 1 month, and shows growth deficiency, (b) does not communicate hunger and lacks interest in food, and (c) the child’s food refusal does not follow a traumatic event and is not due to an underlying medical illness. IA usually emerges during the transition to self-feeding, when the child issues of autonomy are played out daily in the feeding situation. Studies evidence that the feeding interactions between children with IA and their mothers are characterized by low reciprocity, greater interactional conflict and negative affects (Ammaniti et al., 2010, 2012; Chatoor et al., 2000). Moreover, these studies pointed out that maternal depression and eating disorders are frequently associated with IA (Ammaniti et al., 2010; Cooper et al., 2004; Lucarelli et al., 2013). To date, research has focused almost exclusively on the mother–child dyad, while fathers’ involvement, co-parental and family interactions are poorly studied. The current study is a pilot research that investigated mother–father-child triadic interactions, during feeding and play, in families with children diagnosed with IA, in comparison to families with normally developing children. Until now, at the study participated N = 10 families (5 with a child with IA diagnosis and 5 with lack of child’s IA diagnosis, matched for child’s age and gender). The parents-child triadic interactions were assessed in feeding and play contexts using the Lausanne Trilogue Play (Fivaz-Depeursinge and Corboz-Warnery, 1999), adapted to observe father-mother-infant primary triangle in the feeding context, compared to the play context (Lucarelli, Simonelli, and Ammaniti., 2012). Families of the IA-group showed difficulties in expressing and sharing pleasure and positive affects, and in structuring a predictable and flexible context. Children showed little autonomy and difficulty in being actively engaged and tune with parents. Dysfunctional family interactions are a critical issue for IA that affects co-parental and family subsystems, stressing the importance of an articulated diagnostic assessment in order to target effective treatment approaches.